Valuation of Ecobricks as an Artificial Resource in Hardscape Materials - Rahmadhani Fitri; Hendra Fahruddin Siregar; Ayu Erfiana Asmy (Budapest International Research and Critics University, 2021)
The Medan City TPA in the Waterfall Village, Medan Marelan District is the final disposal site for the City of Medan. The composition of the waste at the Waterfall TPA in 2017 consisted of 71.5% organic; Paper 2%; Plastic 10.1%; wood 2%; fabric 2.5% rubber 2.5%; metal 0.6%; glass 0.8%; 1 % chunks; pampers / sanitary napkins 3, 1% and others 3.8% (Department of Hygiene and Parks City Medan). Based on this condition, if waste management efforts are not carried out properly, the service level based on the MDGs (Millineum Development Goals) target of 80% will not be achieved. The composition of plastic waste of 10.1% is quite high. The Ministry of Environment and Forestry (2017) stated that plastic waste increased by 15% from 10% in 2005. The increase will continue in line with the need and use of plastic. Plastic is difficult to decompose, so one thing that can be done is only with 3 R's, namely reuse, reduce and recycle. Reuse by using plastic over and over again, reduce by reducing the use of plastic and recycle by recycling plastic. one of the recycled plastics is with eco-bricks. Ecobricks are a collection of all types of used, clean and dry plastic in used plastic bottles so that they reach a certain density and function as building blocks that can be used over and over again. Ecobrick is a simple solution and simple technology in recycling plastic. Ecobricks can provide direct benefits of Rp. 289,000, - / m2 - Rp. 471.000, - / m2, the price of waste utilization is 57.800-78.500 gr/m2, the price of indirect utilization is Rp. 404,600 – Rp. 549,500 m2